Managing 'belt and road' business disputes a case study of legal problems and solutions - Moser, Michael J.; Bao, Chiann (Kluwer Law International B.V., 2021)
"Managing 'Belt and Road' Business Disputes: A Case Study of Legal Problems and Solutions" is a follow up to the comprehensive "Managing Business Disputes in Today's China: Duelling with Dragons" (2007) guide on foreign direct investments disputes that can arise in the course of initiating and operating a Chinese joint venture. Since its inauguration by the Chinese government in 2013, the "Belt and Road Initiative" (BRI) has included projects in more than 70 countries spanning diverse economic and legal environments. The nature of the BRI coupled with the economic downturn as a result of the COVID-19 pandemic will inevitably generate more challenges than ever. Like its predecessor, this book poses a hypothetical scenario in order to explore the potential issues that may arise from Chinese-foreign business relationships in the BRI context.